(untitled) (Cultura Económica, 2019)
Before national elections took place in October 2007, the terms “social dialogue” and “social pact” acquired increasing importance, as they were understood as necessary political tools for the coming years in Argentina. However, at present, the possibility of signing a social pact is still far away. This article starts introducing the concept and relevance of social dialogue, and reviews the literature that analyzes social pacts in Europe and in other particular countries. After identifying the main factors that explain the rise of social pacts, and highlighting their principal characteristics, this work points out the economic, political and social events that modified their content, and the major threats that they face. Finally, after analysing the particular case of Ireland, this article arrives to some conclusions regarding the necessary conditions for the implementation of a real social pact in Argentina, which guarantees a sustained development.